MARKET POWER AND BANKING LIQUIDITY RISK IN INDONESIA: AN EMPIRICAL STUDY WITH LCR AND NSFR - Syafwan1, Natasha Febrina; Indraswari, Citra Rahayu (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study examines the influence of market power on bank liquidity risk in Indonesia over the period 2019–2023, employing the Liquidity Coverage Ratio (LCR) and Net Stable Funding Ratio (NSFR) as measures of liquidity risk. Market power is proxied through asset, deposit (third-party funds), and loan market shares of 16 conventional commercial banks, which together account for approximately 75% of total industry assets. The empirical analysis is conducted using panel data regression with a Random Effects Model (REM) specification. The findings indicate that asset and deposit market shares exert a significant positive effect on the NSFR, whereas loan market share does not exhibit a statistically significant impact. In contrast, none of the three proxies for market power demonstrate a significant effect on the LCR. These results imply that market power contributes to reducing banks’ long-term liquidity risk, but has no discernible influence on short-term liquidity risk. This research offers important implications for regulators, highlighting the need to incorporate considerations of market structure when designing policies for bank liquidity management.